OP0068 Wisp1 Induces Pathology in Experimental Osteoarthritis and Predicts Disease Progression in Early Osteoarthritis Patients. (15th July 2016) - van den Bosch, M.; Blom, A.; Maeda, A.; Kilts, T.; van den Berg, W.; van Lent, P.; Young, M.; van der Kraan, P.
Abstract : Background: Many osteoarthritis (OA) patients show synovial activation, which is suggested to be involved in joint destruction. Previously, we found strong upregulation of Wnt2b and Wnt16 in the synovium of two experimental OA models. In addition, we found strongly increased Wisp1 expression, a protein induced by canonical Wnt signaling. Objectives: To determine whether there is a relation between WISP1 expression and progression of OA in a cohort study of patients with early symptomatic OA. Furthermore, we will elucidate whether WISP1 plays a role during experimental OA by inducing OA models in wild type (WT) and Wisp1 –/– mice. Methods: Microarray analysis was performed on synovium from patients enrolled in the CHECK study, initiated to follow the progression of early symptomatic OA patients. Expression data were correlated with progression of OA (defined as a decrease in joint space width of ≥1mm and progression of osteophyte formation of ≥4x in size) between baseline and the five-year follow-up measurement. Human end-stage OA synovium was stimulated with WISP1. Joint pathology in WT or Wisp1 –/– mice was assessed by histology after induction of collagenase-induced OA (CIOA), destabilization of the medial meniscus (DMM) and anterior cruciate ligament transection (ACLT) experimental models of OA. The aggrecan neoepitope NITEGE was visualized using immunohistochemistry. Gene expression in the synovial tissue was evaluated using qRT-PCR. Results: Microarray analysis of synovial tissue from patients in the CHECK cohort showed significantly increased WISP1 expression at baseline in OA progressors versus non-progressors. To determine the mechanism of how WISP1 might be involved in OA pathology, we stimulated human OA synovium with WISP1. This increased the expression of MMP2/3/9/13 and ADAMTS4/5 . Next, we determined the in vivo role of WISP1. First, we found that spontaneous cartilage damage was not different between WT and Wisp1 –/– mice at 3, 6 and 12 months of age. Next, we assessed joint pathology 42 days after induction of CIOA in WT and Wisp1 –/– mice. Cartilage damage was significantly decreased in the tibio-femoral joints of the Wisp1 –/– mice as compared with the WT controls. In line with the CIOA, we found significantly decreased cartilage degeneration in the Wisp1 –/– mice in the DMM and ACLT at day 56 after induction. In addition we found decreased expression of Mmp3 / 9 and the aggrecanases Adamts4/5 in the synovium, 7 days after induction of CIOA in Wisp1 –/– mice, in line with the increased expression of these factors after stimulation of human OA synovium with WISP1. Furthermore, the expression of the protease inhibitor Timp1 was decreased in the Wisp1 –/– mice, whereas the expression of Timp3, an important inhibitor of ADAMTS-4/5, was unaffected. Finally, the protease activity in the cartilage, as assessed by the staining of the neoepitope NITEGE, was decreased in the Wisp1 –/– mice. Conclusions: Increased WISP1 expression may play an important role in OA pathology via increased synovial MMP/ADAMTS expression. Furthermore, because of the tight regulation and complexity of Wnt signaling and its role in many physiological processes, targeting WISP1 may more specifically target the OA-related pathological events, while minimizing interference with physiological processes. Disclosure of Interest: None declared